2008
DOI: 10.1371/journal.pbio.0060253
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Reprogramming to Ground State Pluripotency by Signal Inhibition

Abstract: Induced pluripotent stem (iPS) cells are generated from somatic cells by genetic manipulation. Reprogramming entails multiple transgene integrations and occurs apparently stochastically in rare cells over many days. Tissue stem cells may be subject to less-stringent epigenetic restrictions than other cells and might therefore be more amenable to deprogramming. We report that brain-derived neural stem (NS) cells acquire undifferentiated morphology rapidly and at high frequency after a single round of transducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
711
1
18

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 755 publications
(769 citation statements)
references
References 37 publications
25
711
1
18
Order By: Relevance
“…This unexpected finding was consistent with our hypothesis that a stable intermediate phase between fibroblasts and iPSCs could be achieved through the expression of only three reprogramming factors (Oct4, Klf4, and c-Myc). In fact, similar colonies were present in the original discovery [24,32], although subsequently identified differences in potential for reprogramming set these apart [21][22][23].…”
Section: Confirmation Of Two-phase Ipsc Inductionmentioning
confidence: 79%
See 1 more Smart Citation
“…This unexpected finding was consistent with our hypothesis that a stable intermediate phase between fibroblasts and iPSCs could be achieved through the expression of only three reprogramming factors (Oct4, Klf4, and c-Myc). In fact, similar colonies were present in the original discovery [24,32], although subsequently identified differences in potential for reprogramming set these apart [21][22][23].…”
Section: Confirmation Of Two-phase Ipsc Inductionmentioning
confidence: 79%
“…The same genome-wide mapping method has been applied to study the function of Yamanaka factors among ESCs, iPSCs, and what have been termed ''partially reprogrammed cells.'' The last group of cells have ES-like morphology without ES-like pluripotency, following transduction of all four Yamanaka factors [21][22][23]. Examination of these cells can enhance our understanding of reprogramming barriers, but identified molecular mechanisms from comparison of these partially reprogrammed Author Contributions: Z.L.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of iPSCs and subsequent real-time polymerase chain reaction verification were performed as described previously [17]. For immunocytochemical staining, anti-Nanog (1:50, ReproCELL, Yokohama, Japan), anti-Oct3/4 h-134 (1:100, Santa Cruz Biotechnology, Santa Cruz, CA), and anti Sox-2 Y-17 (1:200, Santa Cruz) antibodies were used [18].…”
Section: Materials and Methods Ipsc Generation And Validationmentioning
confidence: 99%
“…Signaling pathways have significant influence on the state of pluripotency. Silva and colleagues showed that neural stem cells could be rapidly converted to iPSCs with only two factors, Oct4 and Klf4, while application of the ERK inhibitor PD0325901 and GSK3 inhibitor CHIR99021 promoted these iPS cells to enter a more authentic ES state, reflected by the reactivation of both X chromosomes and ability to contribute to the germline (Silva et al, 2008).…”
Section: Chemical Compoundsmentioning
confidence: 99%